STUDI ANATOMI DAUN CANTIGI (Vaccinium korinchense Ridl.) PADA ALTITUD BERBEDA DI GUNUNG TALANG - Alponsin, Alponsin; Maideliza, Tesri; Noli, Zozy Aneloi (Metamorfosa: Journal of Biological Sciences, 2017)
The study about leaf anatomy of Bilberry ( Vaccinium korinchense RILD.)  at  altitude gradient on the Talang Mountain has been carried out in October to December 2015. The goal research is to compared that leaf thick tissues Bilbellry at altitude gradient. The sample were collected at Talang Mountain. The research used survey method and purpossive sampling with five altitude gradient (2200-2529 meter above sea level). Leaf section was maked  at the Plant  Structures developments Laboratory, Department Biology, Faculty of Mathematics and Natural Sciences, Andalas University. Data analysis used Kruskal-Wallis test. The results showed that leaf thickness, palisade and spongy thickness various between altitudes is sequentially 434-685 ?m, 183-322 ?m and 175-283 ?m . While epidermis thickness and cuticle thickness did not differ significantly between altitudes.
Keywords: Vaccinium korinchense, Talang Mountain, altitude, leaf anatomy